China Collective Negotiation in COVID-19: What We learn from a Comparative Analysis of China, the United States and Germany - Sun, Xiaohan (American Journal of Trade and Policy, 2020)
Labor conflicts can be solved by an efficient collective bargaining system with consensus-based. Since the economic uncertainty caused by COVID-19, employers have been shut down or have had to reduce operations drastically and many employers want to furlough or dismiss employees under certain circumstances in China. Meanwhile, many workers have lost income. Since workers have gone back to the worksite in March 2020, labor unrest has spread out in order to ask for wage arrears in the manufactory, construction, and service sectors in terms of strikes map from China Labor Bulletin. The paper targets on three different countries with top economies, and examines its bargaining models to keep industrial peace. The paper argues that China bargaining model under state-control strongly depends on government intention for intervention where there is labor unrest, and the system less focuses on self-governance which may result in a hard time to maintain industrial resources, even though the state issued the related policies to highly encouraged companies to hold a negotiation before the lay off workers, reduce wages or work time in order to be employed. While fewer polices and China traditional command-and-control regulation models could not provide an efficient approach to relief labor unrest in the pandemic, Germany's bargaining model is more flexible to provide an example for new governance and co-determination. Also, the bargaining model with sector-level reforms could do more for the United States private sectors in order to the corporation instead of adversarialism. From a comparison among three collective bargaining models, the paper concludes the approaches to protect workers’ rights from global perspectives.
Keywords: globalization; comparative analysis; collective bargaining; strikes; covid-19